(untitled) (Journal of Partial Differential Equations, 2018)
In the study of the regularity criteria for Leray weak solutions to three-dimensional Navier-Stokes equations, two sufficient conditions such that the horizontal velocity u satisfies u∈L^2(0,T;BMO(R^3)) or u∈ L^2/1+r(0,T; B^r_∞,∞(R^3)) for 0 < r < 1 are considered.